2013
DOI: 10.1007/s10096-013-1996-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Borna disease virus infection in neuropsychiatric patients in three western China provinces

Abstract: Borna disease virus (BDV) is a non-cytolytic, neurotropic RNA virus that can infect a wide variety of vertebrate species from birds and primates to humans. Several studies have been carried out to investigate whether BDV is associated with neuropsychiatric diseases. However, this association is still inconclusive. Two panels of subjects consisting of 1,679 various neuropsychiatric patients and healthy people from three western China provinces were enrolled in this study. BDV p24 or p40 RNA in peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
1
23
0
4
Order By: Relevance
“…Previous studies including schizophrenic patients, either using BDV antibody or RNA detection techniques or both, had revealed highly varying prevalence rates between 2.1 % in Poland [25], 12 % in Taiwan [24], 14 % in Germany [20], up to 22 % [26] and 45 % in Japan [23]. A more recent Chinese study found 9.9 % schizophrenic patients RNA-positive by a p24 real-time RT-PCR [29]. Lack of comparability, characteristic for many interesting studies, had not allowed to evaluate correlative evidence, whatsoever, for defined psychiatric diseases and BDV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies including schizophrenic patients, either using BDV antibody or RNA detection techniques or both, had revealed highly varying prevalence rates between 2.1 % in Poland [25], 12 % in Taiwan [24], 14 % in Germany [20], up to 22 % [26] and 45 % in Japan [23]. A more recent Chinese study found 9.9 % schizophrenic patients RNA-positive by a p24 real-time RT-PCR [29]. Lack of comparability, characteristic for many interesting studies, had not allowed to evaluate correlative evidence, whatsoever, for defined psychiatric diseases and BDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Independently, the finding of endogenous Borna-like N protein elements (EBLNs) which had been integrated during million years of co-evolution into germ-lines of humans and their predecessors [1517] promoted the “Mood virus hypothesis” linking BDV with psychiatric diseases [4, 5]. After the early finding of BDV specific antibodies (Ab) in psychiatric patients [18], further worldwide evidence could also be added by the presence of BDV-specific RNA [1929], and importantly by isolation of infectious virus either from blood cells or brain of mentally ill patients [10, 12]. However, differing sensitivity levels of antibody and RNA techniques hampered the comparability of reported infection rates.…”
Section: Introductionmentioning
confidence: 99%
“…BDV is a neurotropic that persists in the central nervous system (2), and affects infected individuals for their entire life span resulting in chronic, persistent infections of neurons and glial cells. It has been reported that BDV infects a range of animal species worldwide (3), including China (4,5). BDV infects neurons in the limbic system, and primarily in the hippocampus and the cortex, which has wide spread connections to diverse cortical areas (6).…”
Section: Introductionmentioning
confidence: 99%
“…BDVs-infection may induce a large spectrum of neuropsychiatric pathologies ranging from immune-mediated neurological disease to non-inflammatory behavioral alterations (Hornig et al, 2003;Ludwig and Bode, 2000;Zhang et al, 2014). According to many disease patterns notably reminiscent of symptoms observed in certain human neuropsychiatric disorders (Hornig et al, 2001), infection in human psychiatric illness has been studied since three decades, but the findings remain controversial (Bode and Ludwig, 2003;Bode et al, 1995;Hornig et al, 2012;Iwata et al, 1998;Rott et al, 1985;Zhang et al, 2013). Notwithstanding, a few human BDV strains have been isolated through co-cultivation of freshly isolated white blood cells from German psychiatric inpatients with a human fetal oligodendroglial cell line (OL cells) .…”
Section: Introductionmentioning
confidence: 99%